Pengaruh Literasi Perpajakan, Love Of Money, Dan Integritas Pribadi Terhadap Niat Patuh Pajak Pada Generasi Z Sebagai Calon Wajib Pajak (Studi Pada Mahasiswa Fakultas Ekonomi Undiksha) - Karuni, Putu Ayu; Herawati, Nyoman Trisna (Vokasi : Jurnal Riset Akuntansi, 2025)
This study was motivated by the phenomenon of low tax compliance rates in Indonesia. Gen Z, represented by students as a productive age group who will become taxpayers in the future, needs special attention regarding their intention to comply with taxes. Findings indicate that there are differences in students' tax compliance intentions influenced by several factors. The factors indicated to influence tax compliance intentions are tax literacy, love of money, and personal integrity. This study uses a quantitative approach with a population of active students in the Faculty of Economics at Ganesha University of Education who have taken tax courses. Using proportional sampling and the Slovin formula, the sample size was 97 students. Primary data was collected through a Likert-scale questionnaire and analyzed using SPSS through descriptive tests, data quality tests, classical assumption tests, and hypothesis tests. The results indicate that tax literacy and personal integrity have a positive and significant effect on tax compliance intentions. The variable “love of money” has a negative and significant effect on tax compliance intention. All three variables simultaneously influence tax compliance intention.